К вопросу о защите права общей долевой собственности - Karas, Yekaterina (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the form of co-ownership in the civil law of the Russian Federation. The author present the concept of sharing property right and the problems related to with a special emphasis on the protection of the right to property, vindication and invalidity of transactions.